A potential flavor seasoning from aquaculture by-products: An example of Takifugu obscurus. (November 2021) - Zhang, Ninglong; Yang, Yunfeng; Wang, Wenli; Fan, Yuxia; Liu, Yuan
Abstract: There is a growing interest in the value utilization of fish by-products. In this study, an advisable method of Takifugu obscurus by-products hydrolysates (F0 ) developed into flavor seasoning was investigated. The F0 were separated into two peptide fractions, >3000 Da (F1 ) and 300–3000 Da (F2 ), and performed Maillard reaction, then flavor characteristics of the Maillard reaction products were comprehensively analyzed. The results showed that the Maillard reaction largely improved flavor profiles of the hydrolysates i.e., enhancing umami taste, volatile aroma, and overall acceptance, while reducing bitterness and fishy smell. Compared with F0 and F1, F2 as the suitable resource of flavor precursors, had the optimal flavor attributes after Maillard reaction. This paper provides a new idea of comprehensive utilization of by-products of pufferfish and guides the preparation of Maillard peptide-based seasoning from fish by-products. Highlights: T. obscurus by-products were utilized by peptide fractions and Maillard reaction. Peptide fraction (300–3000 Da, F2 ) was an advisable resource of flavor precursors. Maillard reaction improved flavor characteristics of T. obscurus by-products. Excellent seasoning can be prepared when F2 involved in the Maillard reaction.